2020
DOI: 10.1002/sim.8760
|View full text |Cite
|
Sign up to set email alerts
|

Optimal multiwave sampling for regression modeling in two‐phase designs

Abstract: Two‐phase designs involve measuring extra variables on a subset of the cohort where some variables are already measured. The goal of two‐phase designs is to choose a subsample of individuals from the cohort and analyse that subsample efficiently. It is of interest to obtain an optimal design that gives the most efficient estimates of regression parameters. In this article, we propose a multiwave sampling design to approximate the optimal design for design‐based estimators. Influence functions are used to compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…In particular, constructing multiphase sampling designs would be a fruitful avenue for future work. (See McIsaac & Cook, 2015, Chen & Lumley, 2020, and Han et al., 2020, for some initial work.) These authors considered designs where a pilot sample could initially be selected from the cohort to obtain information on the validated data that can be used to guide follow‐up sampling waves.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, constructing multiphase sampling designs would be a fruitful avenue for future work. (See McIsaac & Cook, 2015, Chen & Lumley, 2020, and Han et al., 2020, for some initial work.) These authors considered designs where a pilot sample could initially be selected from the cohort to obtain information on the validated data that can be used to guide follow‐up sampling waves.…”
Section: Discussionmentioning
confidence: 99%
“…This research, for example, could build on adaptive strategies that have been proposed for other instances in which key parameters are unknown at the outset, such as that proposed in the context of sample size and power calculations, 36 or that presented for approximating optimal allocation in other settings. 13,29,37,38 Another potential way forward would be to use imputation, following the approaches taken in the analysis of longitudinal data. 24,39 Furthermore, with regard to optimizing for multiple parameters, our simulation study only evaluated the approach in which every parameter is given equal weight (w q = 1 for q = 1, … , p).…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this, we introduce a small rounding threshold, , which can be increased until the sum of the rounded sample sizes is equal to K s . For example, if K s = 40 and (k 00 , k 01 , k 11 , k 10 ) = (20.18, 7.01, 6.49, 6.32), using the standard rounding threshold of 0.5 would yield (k Other approaches have been suggested that directly yield integer solutions, such as the algorithm propose by Wright, 28 and used with good results by Chen and Lumley; 29 we do not consider those here, as our simulations indicate good performance of the continuous allocation strategy combined with the rounding procedure described above.…”
Section: Practical Issuesmentioning
confidence: 99%
“…Recently, Chen et al. 28 have considered a method for incorporation of prior information into multi-wave sampling in a regression framework. Also, further extension to time-dynamic models that introduce time-varying covariates and their time-dependent effects will also provide flexible tools for the two-phase analysis of a broader class of survival models.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of prior information regarding the sampling priorities for certain strata may be an additional way to improve the performance of the adaptive design, particularly in the case of a small phase two sample. Recently, Chen et al 28 have considered a method for incorporation of prior information into multi-wave sampling in a regression framework. Also, further extension to time-dynamic models that introduce time-varying covariates and their time-dependent effects will also provide flexible tools for the two-phase analysis of a broader class of survival models.…”
Section: Discussionmentioning
confidence: 99%